Mitochondrial Pathway Is Involved in Advanced Glycation End Products-Induced Apoptosis of Rabbit Annulus Fibrosus Cells. Issue 10 (15th May 2019) - Hu, Yiqiang; Shao, Zengwu; Cai, Xianyi; Liu, Yunlu; Shen, Min; Yao, Yingtao; Yuan, Tian; Wang, Wentian; Ding, Fan; Xiong, Liming
Abstract : Study Design: Experimental study. Objective: The purposes of this study were to evaluate whether advanced glycation end-products (AGEs) induce annulus fibrosus (AF) cell apoptosis and further to explore the mechanism by which this process occurs. Summary of Background Data: Recent studies revealed that AGEs accumulation is considered an important factor in diabetic intervertebral disc (IVD) degeneration. However, the effect of AGEs on intervertebral disc remains unclear. Methods: AF cells were treated with various concentrations of AGEs for 3 days. Cell viability and cell proliferation were measured by Cell Counting Kit-8 (CCK-8) and 5-ethynyl-2′-deoxyuridine (EdU) incorporation assays, respectively. Cell apoptosis was examined by Annexin V/PI apoptosis detection kit and Hoechst 33342. The expression of apoptosis-related proteins, including Bax, Bcl-2, cytochrome c, caspase-3, and caspase-9, was detected by western blotting. In addition, Bax and Bcl-2 mRNA expression levels were detected by real-time PCR (RT-PCR). Mitochondrial membrane potential (MMP) and intracellular reactive oxygen species (ROS) production of AF cell were examined by 5, 5′, 6, 6′ -Tetrachloro-1, 1′, 3, 3′- tetraethyl-imidacarbocyanine iodide (JC-1) staining and 2′, 7′-Dichlorodihydrofluorescein diacetate (DCFH-DA) fluorescent probes, respectively. Results: Our results indicated that AGEs had inhibitory effects on AF cell proliferation and induced AF cell apoptosis. The molecular data showed that AGEs significantly up-regulated Bax expression and inhibited Bcl-2 expression. In addition, AGEs increased the release of cytochrome c into the cytosol and enhanced caspase-9 and caspase-3 activation. Moreover, treatment with AGEs resulted in a decrease in MMP and the accumulation of intracellular ROS in AF cells. The antioxidant N-acetyl-L-cysteine (NAC) significantly reversed AGE-induced MMP decrease and AF cell apoptosis. Conclusion: These results suggested that AGEs induce rabbit AF cell apoptosis and mitochondrial pathway may be involved in AGEs-mediated cell apoptosis, which may provide a theoretical basis for diabetic IVD degeneration. Level of Evidence: N/A Abstract : Advanced glycation end-products (AGEs) can induce rabbit annulus fibrosus (AF) cell apoptosis and mitochondrial pathway may be involved in AGEs-mediated cell apoptosis. The antioxidant N-acetyl-L-cysteine significantly reversed AGE-induced AF cell apoptosis. This research may provide a theoretical basis for diabetic intervertebral disc degeneration.